ALLERGIC FUNGAL RHINOSINUSITIS IN PATIENTS WITH NASAL POLYPOSIS (Iraqi Journal of Medical Sciences, 2017)
Background: Nasal polyposis and chronic rhinosinusitis is much debated subject. Generally speaking, nasal polyposis should probably be regarded as one form of chronic inflammation in the nose and sinuses, which is indeed part of the spectrum of chronic rhinosinusitis. Nasal polyposis is the ultimate form of inflammation for unknown reasons; polyps preferentially develop in subtypes of inflammatory diseases. Allergic fungal rhinosinusitis (AFRS) is defined the consequence of immunocompetent patient whenever there is allergy to fungus.Objective: To determine the frequency of allergic fungal rhinosinusitis among patients having nasal polyposis.Methods: A prospective study of 60 selected patients with nasal polyposis was studied at Al-Imamein Al-Kadhimein Medical City. After thorough history and full ENT examination, all patients sent for computed tomography (CT) scan of the nose and paranasal sinuses. Patients who needed surgical treatment, the specimens were sent for histopathological analysis to identify the fungi. The diagnosis of allergic fungal sinusitis was based on analysis of clinical, radiological, and laboratory investigations. Results: The mean age was (41.3±13.7) years; male to female ratio was (1.7:1). Both nasal obstruction 54 (90%) and nasal discharge 51 (85%) were the commonest clinical presentation. CT scans opacities were found in all 60 patients (100%). Fungal elements were detected by histopathological study in 7 (11.7%) of them.Conclusion: Allergic fungal rhinosinusitis is a significant cause of nasal polyposis.Keywords: Allergy, fungal infection, nasal polyposis. DOI: 10.22578/IJMS.14.4.11
Keywords: Allergy; fungal infection; nasal polyposis